Fe-Pt-C based sputtering target member, sputtering target assembly, film formation method, and method for manufacturing sputtering target member

By utilizing a Fe-Pt-C sputtering target member with a carbon-derived diffraction peak at a specific angle range, the issue of particle generation during sputtering is addressed, enhancing the yield of high-quality magnetic thin films.

JP7657960B2Active Publication Date: 2025-04-07JX NIPPON MINING & METALS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023557652
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-05
Filing Date
2022-09-22
Publication Date
2025-04-07
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

Existing sputtering technologies face challenges in suppressing particle generation during the sputtering of Fe-Pt-C target members, particularly due to the desorption of nonmagnetic materials like carbon, which can lead to abnormal discharge and particle formation.

Method used

A Fe-Pt-C sputtering target member with a carbon-derived diffraction peak at a specific angle range (25.6°≦2θ≦26.2°) is used, which reduces particle generation by altering the carbon's crystal structure and improving the target's sputtering characteristics.

Benefits of technology

The proposed solution effectively suppresses particle generation during sputtering, improving the production yield of granular structure magnetic thin films with a Fe-Pt magnetic phase.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Provided is a Fe-Pt-C-based sputtering target member which is prevented from the formation of particles during sputtering. The Fe-Pt-C-based sputtering target member has a magnetic phase containing Fe and Pt and a non-magnetic phase, the sputtering target member having a carbon-derived diffraction peak at a diffraction angle satisfying the formula: 25.6° ≤ 2θ ≤ 26.2° in an X-ray diffraction profile produced by the analysis of the sputtering target member by an X-ray diffraction method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] In one embodiment, the present invention relates to an Fe-Pt-C based sputtering target member. In another embodiment, the present invention relates to a sputtering target assembly including such a sputtering target member. In yet another embodiment, the present invention relates to a film formation method using such a sputtering target member. In yet another embodiment, the present invention relates to a method for manufacturing a sputtering target member. [Background technology]

[0002] In the field of magnetic recording, as represented by hard disk drives, materials based on ferromagnetic metals Co, Fe, or Ni are used as materials for magnetic thin films that perform recording. For example, Co-Cr and Co-Cr-Pt ferromagnetic alloys with Co as the main component have been used for the recording layer of hard disks that employ in-plane magnetic recording. In addition, composite materials in which non-magnetic particles such as oxides and carbon are dispersed in Co-Cr-Pt ferromagnetic alloys with Co as the main component are often used for the recording layer of hard disks that employ perpendicular magnetic recording, which has been put to practical use in recent years. Due to the high productivity, magnetic thin films are often produced by sputtering sputtering target members containing the above materials using a DC magnetron sputtering device.

[0003] On the other hand, the recording density of hard disks is increasing rapidly year by year, and is currently 1 Tbit / in 2 Devices with capacities exceeding 1Tbit / in are becoming commercially available. 2 When the recording density reaches 100 nm, the size of the recording bit will be less than 10 nm, and in that case, it is expected that superparamagnetism due to thermal fluctuation will become a problem, and it is expected that the materials currently used for magnetic recording media, for example, materials in which Pt is added to Co-Cr-based alloys to increase the magnetocrystalline anisotropy, will not be sufficient. This is because magnetic particles that behave stably as ferromagnetic at sizes of 10 nm or less need to have higher magnetocrystalline anisotropy.

[0004] For the above reasons, L1 0 The Fe-Pt magnetic phase with the L1 structure is attracting attention as a material for ultra-high density recording media. 0 The Fe-Pt magnetic phase with this structure has high crystal magnetic anisotropy as well as excellent corrosion resistance and oxidation resistance, and is therefore expected to be a suitable material for use in magnetic recording media. When using the Fe-Pt magnetic phase as a material for ultra-high density recording media, there is a demand for the development of technology that can disperse ordered Fe-Pt magnetic particles as densely as possible with uniform orientation while being magnetically isolated.

[0005] For this reason, L1 0 A granular-structure magnetic thin film in which the Fe-Pt magnetic phase is isolated by non-magnetic materials such as oxides, nitrides, carbides, and carbon has been proposed for use in the magnetic recording media of next-generation hard disks that employ a thermally assisted magnetic recording method. This granular-structure magnetic thin film has a structure in which the magnetic particles are magnetically insulated from each other by the presence of non-magnetic materials.

[0006] However, when sputtering a sputtering target member containing a non-magnetic material in the alloy using a sputtering device, there is a problem that the non-magnetic material may be inadvertently detached during sputtering, or abnormal discharge may occur starting from vacancies contained in the sputtering target member, resulting in the generation of particles. In particular, when carbon is used as the non-magnetic material, there is a problem that carbon is a material that is difficult to sinter, and carbon easily forms aggregates with itself. Therefore, there is a problem that carbon lumps easily detach during sputtering, and a large number of particles are generated on the film after sputtering.

[0007] To solve this problem, in Patent Document 1 (Patent Publication No. 5497904), the crystallinity of carbon materials is evaluated by Raman scattering spectroscopy, vibration modes called the G band and the D band are measured, and the peak intensity ratio between the G band and the D band (I G / I D) is 5.0 or less. In contrast, in Patent Document 2 (Patent Publication No. 5592022), the peak intensity ratio of the G band to the D band (I G / I D ) is 5.0 or more. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 5497904 [Patent Document 2] Patent No. 5592022 Summary of the Invention [Problem to be solved by the invention]

[0009] The techniques described in the above patent documents can reduce particle generation during sputtering of Fe-Pt-C-based sputtering target members. However, providing a different method for suppressing particle generation in Fe-Pt-C-based sputtering target members would be useful in expanding the possibilities for future technological development in this technical field.

[0010] Therefore, in one embodiment, an object of the present invention is to provide an Fe-Pt-C based sputtering target member that can suppress the generation of particles during sputtering by a method different from the conventional method. In another embodiment, an object of the present invention is to provide a sputtering target assembly including such a sputtering target member. In yet another embodiment, an object of the present invention is to provide a film formation method using such a sputtering target member. In yet another embodiment, an object of the present invention is to provide a method for manufacturing such an Fe-Pt-C based sputtering target member. [Means for solving the problem]

[0011] In order to solve the above problems, the present inventors have intensively studied. As a result, in the structural analysis by X-ray diffraction method, a carbon-containing Fe-Pt-C sputtering target member having a diffraction peak (peak top) at a diffraction angle shifted from that of ordinary graphite is effective in reducing the number of particles. The present invention has been completed based on such findings and is exemplified below.

[0012] [1] An Fe-Pt-C sputtering target member having a magnetic phase containing Fe and Pt and a non-magnetic phase containing C, wherein in the X-ray diffraction profile obtained by analyzing the sputtering target member by X-ray diffraction method, an Fe-Pt-C sputtering target member having a diffraction peak derived from carbon at a diffraction angle satisfying 25.6° ≤ 2θ ≤ 26.2°. [2] In the X-ray diffraction profile obtained by analyzing the sputtering target member by X-ray diffraction method, the integrated intensity I at a diffraction angle in the range of 25.6° ≤ 2θ ≤ 26.2° 1 with respect to the integrated intensity I at a diffraction angle in the range of 26.3° ≤ 2θ ≤ 27.0° 0 The ratio of is 0 to 0.5, and the Fe-Pt-C sputtering target member according to [1]. [3] The Fe-Pt-C sputtering target member according to [1] or [2], containing 5 at.% to 70 at.% of Pt and 1 at.% to 70 at.% of C, and the total concentration of Fe, Pt and C being 90 at.% or more. [4] The Fe-Pt-C sputtering target member according to [1] or [2], containing 5 at.% to 70 at.% of Pt and 1 at.% to 70 at.% of C, and the balance being composed of Fe and unavoidable impurities. [5] A sputtering target assembly comprising: the sputtering target member according to any one of [1] to [4]; and a backing tube or a backing plate joined to the sputtering target member. [6] A film forming method comprising sputtering the sputtering target member according to any one of [1] to [4]. [7] A step of preparing a mixed powder containing one or both of the following combinations of (1) and (2); (1) A combination of one or both of graphene powder and graphene oxide powder, and Fe-Pt alloy powder (2) A combination of one or both of graphene powder and graphene oxide powder, Fe powder, and Pt powder A step of pressure sintering the mixed powder; A method for producing a sputtering target member comprising the steps of: Effect of the Invention

[0013] By performing sputtering using the Fe-Pt-C based sputtering target member according to one embodiment of the present invention, it is possible to suppress the generation of particles during sputtering. By using the sputtering target member according to one embodiment of the present invention, it is possible to obtain a special effect of improving the manufacturing yield of a granular structure magnetic thin film having, for example, an Fe-Pt magnetic phase. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (1.Magnetic phase) A sputtering target member according to one embodiment of the present invention has a magnetic phase containing Fe and Pt. In the magnetic phase, Fe and Pt can exist as simple substances or in the form of an Fe-Pt alloy. The magnetic phase may contain other alloying elements. In one embodiment, the magnetic phase containing Fe and Pt can have a composition consisting of 5 to 70 at.% Pt, the balance being Fe and unavoidable impurities, or can have a composition consisting of 5 to 60 at.% Pt, the balance being Fe and unavoidable impurities. In another embodiment, the magnetic phase containing Fe and Pt may have a composition consisting of 5 to 70 at.% Pt, 20 at.% or less in total of one or more third elements selected from Ge, Au, Ag, B, Co, Cr, Cu, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Sn, Ta, W, V, and Zn, the balance being Fe and unavoidable impurities, or may have a composition consisting of 5 to 60 at.% Pt, 20 at.% or less in total of one or more third elements selected from Ge, Au, Ag, B, Co, Cr, Cu, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Sn, Ta, W, V, and Zn, the balance being Fe and unavoidable impurities.

[0015] From the viewpoint that the magnetic phase containing Fe and Pt is likely to assume the form of an ordered alloy phase, the atomic concentration of Pt in the magnetic phase is preferably 35 at.% or more, more preferably 40 at.% or more, and even more preferably 45 at.% or more. For the same reason, the atomic concentration of Pt in the magnetic phase is preferably 55 at.% or less, more preferably 53 at.% or less, and even more preferably 52 at.% or less.

[0016] In addition, Ge, Au, Ag, B, Co, Cr, Cu, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Sn, Ta, W, V and Zn have the effect of lowering the heat treatment temperature for ordering the magnetic phase containing Fe and Pt, and may also have other effects, such as increasing the magnetocrystalline anisotropy energy and coercive force, so they may be actively added. From the viewpoint of significantly exerting the effect, the concentration of these third elements contained in the magnetic phase is preferably 1 at.% or more in total, more preferably 2.5 at.% or more in total, and even more preferably 5 at.% or more in total. In addition, from the viewpoint of obtaining sufficient magnetic properties as a magnetic thin film when sputtered, the concentration of these third elements in the magnetic phase is preferably 20 at.% or less in total, more preferably 15 at.% or less in total, and even more preferably 10 at.% or less in total. Note that these third elements may not only be present in the magnetic phase, but may also be present separately from the magnetic phase as a single phase. Whether the third element is present in the magnetic phase containing Fe and Pt or as a separate phase can be determined by performing element mapping using an EPMA or the like.

[0017] The total concentration of these third elements in the sputtering target member, including both the case where the third elements are present in the Fe-Pt alloy phase and the case where they are present as a single phase, is preferably 0.5 at.% or more, more preferably 2 at.% or more, and even more preferably 4 at.% or more, for the same reasons as above. Also, the total content of these third elements in the sputtering target member is preferably 15 at.% or less, more preferably 12.5 at.% or less, and even more preferably 10 at.% or less, for the same reasons as above.

[0018] (2. Non-magnetic phase) A sputtering target member according to one embodiment of the present invention has a non-magnetic phase containing C (carbon). The non-magnetic phase can be present in a dispersed state in the magnetic phase containing Fe and Pt described above. C constituting the non-magnetic phase has a characteristic crystal structure. As a result, in an X-ray diffraction profile obtained by analyzing the sputtering target member by an X-ray diffraction method, a diffraction peak derived from carbon is present at a diffraction angle that satisfies 25.6°≦2θ≦26.2°, typically 25.8°≦2θ≦26.0°. By having a diffraction peak in this diffraction angle range, particles during sputtering are suppressed.

[0019] In an X-ray diffraction profile obtained by analyzing graphite by an X-ray diffraction method, a diffraction peak is observed at a diffraction angle in the range of 26.3°≦2θ≦27.0°, but the sputtering target member according to this embodiment contains C with this diffraction peak shifted to the lower angle side. Therefore, it can be said that the crystal structure of C constituting the nonmagnetic phase of the sputtering target member according to this embodiment is different from that of normal graphite. Graphite includes exfoliated graphite, expanded graphite, scaly graphite, and flake graphite.

[0020] The sputtering target member according to one embodiment of the present invention may partially contain graphite, but it is preferable that the amount of graphite is small. Specifically, the sputtering target member according to one embodiment of the present invention has an integrated intensity I 1 Integrated intensity I at diffraction angles in the range of 26.3°≦2θ≦27.0° 0 The ratio (I 0 / I 1 ) is 0 to 0.5, typically 0 to 0.2, more typically 0 to 0.1, and even more typically 0.

[0021] In the present invention, the method for analyzing the structure of a sputtering target member by X-ray diffraction is as follows. Analytical equipment: X-ray diffraction equipment (in the examples, Rigaku Corporation's fully automatic horizontal multipurpose X-ray diffraction equipment SmartLab was used) Tube: Cu (measured with CuKα) Tube voltage: 40kV Tube current: 30mA Optical system: Focused diffraction optical system Scan mode: 2θ / θ Scanning range (2θ): 10°~90° Measurement step (2θ): 0.02° Scan speed (2θ): 0.5° per minute Attachment: Standard attachment Filter: CuKβ filter Counter monochrome: None Counter: D / teX Ultra Divergence slit: 2 / 3deg. Divergence vertical slit: 10.0 mm Scattering slit: 10.0 mm Receiving slit: 10.0 mm Attenuator: OPEN Measurement sample size: Approx. 20mm x 15mm (measurement surface) The analysis may be performed on any measurement surface of the sputtering target member. For example, it may be the sputter surface, a cross section parallel to the sputter surface, or a cross section perpendicular to the sputter surface. The measurement surface is polished in order using abrasive cloths with grit sizes ranging from P80 to P2000 based on the FEPA standard, and finally buffed using aluminum oxide abrasive grains with a particle size of about 0.3 μm. In the embodiment, the analysis of the obtained XRD profile was performed using the integrated powder X-ray analysis software PDXL (version 1.6.0.0) manufactured by Rigaku Corporation. Here, a peak search was performed by automatic profile processing on the obtained measurement data, and the peak position and integrated intensity were calculated. In the peak search, background subtraction and Kα 2After removing and smoothing, peaks are detected using the second-order differential method. In the second-order differential method, peaks whose intensity is deemed insufficient relative to the error are discarded and not detected. In addition, the peak shape is represented by a divided pseudo-Voigt function, and the peak position, half-width, integrated intensity, etc. can be calculated. The methods and conditions for each process in the peak search are shown below. Background subtraction: Polynomial fitting method (peak width threshold 1.00, intensity threshold 10.00) Kα 2 Removal: Rachinger method (intensity ratio 0.5) Smoothing: B-spline smoothing method (smoothing parameter 10.00, points 3, x-threshold 1.5) From the results of the peak search, the presence or absence of a diffraction peak in the range of 25.6°≦2θ≦26.2° is examined.

[0022] The sputtering target member according to one embodiment of the present invention may contain, as a non-magnetic material, at least one or more selected from carbides, oxides, nitrides, and carbonitrides in addition to C. The non-magnetic material may be present in the sputtering target member in a dispersed state as a non-magnetic phase that is distinguishable from the Fe-Pt alloy phase. Examples of carbides include one or more carbides of elements selected from B, Ca, Nb, Si, Ta, Ti, W, and Zr. Examples of oxides include one or more oxides of elements selected from Si, Al, B, Ba, Be, Ca, Ce, Cr, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr. Examples of nitrides include one or more nitrides of elements selected from B, Al, Ca, Nb, Si, Ta, Ti, and Zr. Examples of carbonitrides include carbonitrides of one or more elements selected from Ti, Cr, V, and Zr. These non-magnetic materials may be added as appropriate depending on the required magnetic properties of the magnetic thin film.

[0023] (3. Overall composition) A sputtering target member according to one embodiment of the present invention contains 5 at.% to 70 at.% Pt and 1 at.% to 70 at.% C. A sputtering target member according to another embodiment of the present invention contains 10 at.% to 60 at.% Pt and 2 at.% to 60 at.% C. A sputtering target member according to yet another embodiment of the present invention contains 20 at.% to 50 at.% Pt and 5 at.% to 50 at.% C. A sputtering target member according to yet another embodiment of the present invention contains 20 at.% to 40 at.% Pt and 30 at.% to 50 at.% C. In each of the above embodiments, the total concentration of Fe, Pt and C can be 90 at.% or more, 95 at.% or more, 98 at.% or more, or 99 at.% or more.

[0024] In each of the above embodiments, there is no upper limit to the total concentration of Fe, Pt, and C, and the sputtering target member may be composed of only Fe, Pt, and C, excluding unavoidable impurities. Thus, the sputtering target member according to one embodiment of the present invention contains 5 at.% to 70 at.% Pt, 1 at.% to 70 at.% C, and the balance is Fe and unavoidable impurities. The sputtering target member according to another embodiment of the present invention contains 10 at.% to 60 at.% Pt, 2 at.% to 60 at.% C, and the balance is Fe and unavoidable impurities. The sputtering target member according to yet another embodiment of the present invention contains 20 at.% to 50 at.% Pt, 5 at.% to 50 at.% C, and the balance is Fe and unavoidable impurities. A sputtering target member according to yet another embodiment of the present invention contains 20 at. % to 40 at. % Pt, 30 at. % to 50 at. % C, and the balance being Fe and unavoidable impurities.

[0025] In each of the above embodiments, elements that can be added to the sputtering target member other than Fe, Pt, and C include one or more third elements selected from the above-mentioned Ge, Au, Ag, B, Co, Cr, Cu, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Sn, Ta, W, V, and Zn, as well as one or more carbides, oxides, nitrides, and carbonitrides.

[0026] (4. Relative Density) In one embodiment of the sputtering target member according to the present invention, the relative density is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The relative density can be, for example, 80% to 95%, or can be 80% to 90%. In this specification, the relative density is a value obtained by dividing the measured density of the sputtering target member by the calculated density (also called the theoretical density). The measured density is measured by Archimedes' method. The calculated density is the density when it is assumed that the constituent components of the raw material powder of the target member are mixed without diffusing or reacting with each other, and is calculated by the following formula. Formula: Calculated density = Σ (molecular weight of the component of the raw powder × molar concentration of the component of the raw powder) / Σ (molecular weight of the component of the raw powder × molar concentration of the component of the raw powder / literature value density of the component of the raw powder) Here, Σ means taking the sum of all the constituent components of the target member other than the impurities.

[0027] (5. Manufacturing Method) A sputtering target member according to an embodiment of the present invention can be produced by using a powder sintering method, for example, by the following method. First, Fe powder, Pt powder, Pt-Fe alloy powder, and optionally powder of a third element are prepared as metal powders. The powder of the third element may be provided in the form of an alloy powder with Fe and / or Pt. These metal powders may be produced by pulverizing a melted and cast ingot, or may be produced as an atomized powder.

[0028] In addition, as the powder of the non-magnetic material, in addition to carbon powder, carbide powder, nitride powder, oxide powder, carbonitride powder, etc. are prepared as necessary. In this case, it is preferable to use graphene powder or graphene oxide powder as the carbon powder.

[0029] Next, raw material powders (metal powder and non-magnetic material powder) are weighed out to obtain a desired composition, and mixed and pulverized using a known method such as a ball mill, thereby preparing a mixed powder containing one or both of the following combinations (1) and (2). (1) A combination of one or both of graphene powder and graphene oxide powder, and Fe-Pt alloy powder (2) A combination of one or both of graphene powder and graphene oxide powder, Fe powder, and Pt powder At this time, it is desirable to seal an inert gas in the grinding container to suppress oxidation of the raw material powder as much as possible. 2 Gas is one example.

[0030] From the viewpoint of realizing a uniform structure, the median diameter (D50) in the volumetric particle size distribution of the raw material mixed powder is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less. On the other hand, from the viewpoint of suppressing composition changes due to oxidation of the raw material mixed powder, the median diameter is preferably 0.3 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more.

[0031] In the present invention, the median diameter of the raw material mixed powder means the particle size at 50% cumulative volume (D50) in the particle size distribution obtained by a laser diffraction / scattering method. In the examples, a particle size distribution measuring device (Model LA-920, manufactured by Horiba, Ltd.) was used to disperse the powder in an ethanol solvent and measure it. The refractive index used was the value of metallic platinum.

[0032] The mixed powder thus obtained is molded and sintered in a vacuum or inert gas atmosphere by hot pressing. In addition to hot pressing, various pressure sintering methods such as plasma discharge sintering can be used. In particular, hot isostatic sintering (HIP) is effective in increasing the density of the sintered body, and it is preferable to carry out hot pressing and hot isostatic sintering (HIP) in this order from the viewpoint of increasing the density of the sintered body.

[0033] The holding temperature during sintering may be appropriately set depending on the composition of the sputtering target member, but in order to prevent the crystal grains from becoming coarse, it is preferably set to 1500° C. or less, more preferably 1400° C. or less, and even more preferably 1200° C. or less. In order to improve the density of the sintered body, the holding temperature during sintering is preferably set to 600° C. or more, more preferably 700° C. or more, and even more preferably 750° C. or more.

[0034] The pressing pressure during sintering is preferably 20 MPa or more, more preferably 25 MPa or more, and even more preferably 30 MPa or more in order to promote sintering, and is preferably 70 MPa or less, more preferably 50 MPa or less, and even more preferably 40 MPa or less, in consideration of the strength of the die.

[0035] The sintering time is preferably 0.3 hours or more, more preferably 0.5 hours or more, and even more preferably 1.0 hour or more in order to improve the density of the sintered body, and is preferably 5.0 hours or less, more preferably 4.0 hours or less, and even more preferably 3.0 hours or less in order to prevent the crystal grains from becoming coarse.

[0036] The resulting sintered body is processed into a desired shape using a lathe or the like to produce a sputtering target member according to one embodiment of the present invention. There are no particular limitations on the target shape, but examples include a flat plate shape (including a disk shape and a rectangular plate shape) and a cylindrical shape. The sputtering target member according to one embodiment of the present invention is particularly useful as a sputtering target member used for depositing a granular structure magnetic thin film.

[0037] The sputtering target member may be attached to a substrate such as a backing plate or a backing tube as necessary and mounted in a sputtering apparatus as a sputtering target assembly. The sputtering target member may be mounted in a sputtering apparatus as a sputtering target without using a substrate.

[0038] (6. Film formation method) In one embodiment, the present invention provides a film formation method including a step of sputtering using the sputtering target member. Sputtering conditions can be appropriately set. For example, the film formation method can form a magnetic thin film having a granular structure. EXAMPLES

[0039] Examples of the present invention will be described below together with comparative examples. However, the examples and comparative examples are provided for a better understanding of the present invention and its advantages, and are not intended to limit the present invention.

[0040] Example 1 <Preparation of sputtering target components> As raw powders, Fe powder (nominal purity 99.9 at.%), Pt powder (nominal purity 99.9 at.%), and graphene powder were purchased and weighed to have an atomic ratio of Fe:Pt:C = 30:30:40. Next, the weighed powders were put into a ball mill together with zirconia balls as a grinding medium, and mixed and ground in an Ar atmosphere. The volumetric particle size distribution of the ground raw mixed powder was determined using a laser diffraction particle size distribution analyzer (manufacturer: Horiba, Ltd., model: LA-920), and the median diameter was calculated to be 8.6 μm. Next, the raw material powder mixture removed from the media stirring mill was filled into a carbon mold and sintered in a vacuum atmosphere by hot pressing. Next, the sintered body removed from the hot pressing mold was subjected to hot isostatic sintering (HIP). The hot pressing was performed at a holding temperature of 700-1400°C and a pressing pressure of 20-30 MPa for 1-2 hours. After the hot pressing, hot isostatic pressing (HIP) was performed to increase density. The relative density of the obtained sintered body was 87.9%.

[0041] Next, each sintered body was cut using a lathe into a shape having a diameter of 180.0 mm and a thickness of 5.0 mm to obtain a disk-shaped sputtering target member.

[0042] <Structural analysis> The sputtering surface of the sputtering target member obtained by the above manufacturing procedure was polished under the conditions described above. The structure of the polished sputtering surface was analyzed under the conditions described above using an X-ray diffractometer (XRD) of Rigaku Corporation, model SmartLab. As a result, it was found that there was a diffraction peak derived from carbon at a diffraction angle of 2θ=25.9°. In addition, in the obtained X-ray diffraction profile, the integrated intensity I 1 Integrated intensity I at diffraction angles in the range of 26.3°≦2θ≦27.0° 0 The ratio (I 0 / I 1 ) was 0. Note that structural analysis by XRD was also performed on a cross section perpendicular to the sputtered surface, but no difference was observed.

[0043] <Film formation test> The sputtering target member obtained by the above manufacturing procedure was attached to a magnetron sputtering device (C-3010 sputtering system manufactured by Canon Anelva Corporation), and sputtering was carried out. The sputtering conditions were an input power of 1 kW and an Ar gas pressure of 1.7 Pa. After a total of 2 hours of pre-sputtering, a film was formed on a 4-inch diameter silicon substrate for 20 seconds. The number of particles (particle size 0.09 to 3 μm) adhering to the substrate was measured using a particle counter (manufactured by KLA-Tencor, device name: Candela CS920). As a result, the number of particles detected was 60.

[0044] Comparative Example 1 <Preparation of sputtering target components> The raw material powders were prepared, mixed, and pulverized under the same conditions as in Example 1, except that commercially available graphite powder was used as the carbon powder. The volumetric particle size distribution of the pulverized raw material mixed powder was determined under the same conditions as in Example 1, and the median diameter was calculated to be 7.3 μm. Next, the raw material mixed powder taken out of the median stirring mill was subjected to hot pressing and HIP under the same conditions as in Example 1. The relative density of the sintered body was 92.7%. Next, each sintered body was cut using a lathe into a shape of 180.0 mm in diameter and 5.0 mm in thickness to obtain a disk-shaped sputtering target member.

[0045] <Structural analysis> The sputtering surface of the sputtering target member obtained by the above manufacturing procedure was subjected to XRD analysis in the same manner as in Example 1. As a result, it was found that there was no diffraction peak derived from carbon at a diffraction angle in the range of 25.6°≦2θ≦26.2°, but instead there was a diffraction peak derived from carbon at a diffraction angle of 2θ=26.6°. In addition, in the obtained X-ray diffraction profile, the integrated intensity I 1 Integrated intensity I at diffraction angles in the range of 26.3°≦2θ≦27.0° 0 The ratio (I 0 / I 1 ) could not be calculated because the denominator is 0.

[0046] <Film formation test> Using the sputtering target member obtained by the above manufacturing procedure, sputtering was carried out under the same conditions as in Example 1. The number of detected particles was 200.

[0047] Comparative Example 2 <Preparation of sputtering target components> Raw material powders were prepared, mixed, and pulverized under the same conditions as in Example 1, except that commercially available graphite powder (the same graphite powder as in Example 4 of Patent No. 5592022) was used as the carbon powder. The volumetric particle size distribution of the pulverized raw material mixed powder was determined under the same conditions as in Example 1, and the median diameter was calculated to be 25.5 μm. Next, the raw material mixed powder taken out from the media stirring mill was subjected to hot pressing and HIP under the same conditions as in Example 1. The relative density of the sintered body was 93.4%. Next, each sintered body was cut using a lathe into a shape of 180.0 mm in diameter and 5.0 mm in thickness to obtain a disk-shaped sputtering target member.

[0048] <Structural analysis> The sputtering surface of the sputtering target member obtained by the above manufacturing procedure was subjected to XRD analysis in the same manner as in Example 1. As a result, it was found that there was no diffraction peak derived from carbon at a diffraction angle in the range of 25.6°≦2θ≦26.2°, but instead there was a diffraction peak derived from carbon at a diffraction angle of 2θ=26.6°. In addition, in the obtained X-ray diffraction profile, the integrated intensity I 1 Integrated intensity I at diffraction angles in the range of 26.3°≦2θ≦27.0° 0 The ratio (I 0 / I 1 ) could not be calculated because the denominator is 0.

[0049] <Film formation test> Using the sputtering target member obtained by the above manufacturing procedure, sputtering was carried out under the same conditions as in Example 1. The number of particles detected was 1,000.

[0050] From the results of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that by using an Fe-Pt-C-based sputtering target member having a carbon-derived diffraction peak at a specified diffraction angle, particles during sputtering can be significantly suppressed. The number of particles during sputtering was larger in Comparative Example 2, which used carbon powder with a larger median diameter than in Comparative Example 1. If this tendency is applied to Comparative Example 1 and Example 1, it is predicted that the number of particles during sputtering would be similar or smaller in Comparative Example 1. However, in reality, the number of particles during sputtering was significantly reduced in Example 1 compared to Comparative Example 1. This difference is considered to be due to the fact that the sputtering target member in Example 1 had a carbon-derived diffraction peak at a diffraction angle that satisfied 25.6°≦2θ≦26.2°.

Claims

1. An Fe-Pt-C based sputtering target member having a magnetic phase containing Fe and Pt and a non-magnetic phase containing C, wherein an X-ray diffraction profile obtained by analyzing the sputtering target member by an X-ray diffraction method has a diffraction peak derived from carbon at a diffraction angle that satisfies 25.6°≦2θ≦26.2°.

2. In the X-ray diffraction profile obtained by analyzing the sputtering target member by X-ray diffraction method, the integrated intensity I 1 The integrated intensity I at a diffraction angle in the range of 26.3°≦2θ≦27.0° 0 2. The Fe-Pt-C based sputtering target member according to claim 1, wherein the ratio of is 0 to 0.

5.

3. 3. The Fe-Pt-C based sputtering target member according to claim 1 or 2, containing 5 at. % to 70 at. % of Pt and 1 at. % to 70 at. % of C, and the total concentration of Fe, Pt and C is 90 at. % or more.

4. 3. The Fe-Pt-C based sputtering target member according to claim 1, comprising 5 at. % to 70 at. % of Pt, 1 at. % to 70 at. % of C, and the balance consisting of Fe and unavoidable impurities.

5. 3. A sputtering target assembly comprising the sputtering target member according to claim 1 or 2, and a backing tube or a backing plate joined to the sputtering target member.

6. A film forming method comprising sputtering the sputtering target member according to claim 1 or 2.

7. A step of preparing a mixed powder containing one or both of the following combinations of (1) and (2); (1) A combination of one or both of graphene powder and graphene oxide powder, and Fe—Pt alloy powder (2) A combination of one or both of graphene powder and graphene oxide powder, Fe powder, and Pt powder A step of pressure sintering the mixed powder; A method for producing a sputtering target member comprising the steps of:

Citation Information

Patent Citations

  • Luggprovided tire and wheel employing such tire

    JP1979097904A

  • Flip flop circuit

    JP1980092022A

  • Fe-Pt BASED SPUTTERING TARGET AND METHOD FOR MANUFACTURING THE SAME

    JP2020180365A

  • Sputtering target for magnetic recording film

    WO2013190943A1

  • Sputtering target for forming magnetic recording film and process for producing same

    WO2014013920A1